2016
DOI: 10.1016/s2214-109x(16)30187-5
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and second-hand smoke exposure in young adolescents aged 12–15 years: data from 68 low-income and middle-income countries

Abstract: This work was partly supported by the Young Scholars Program of Shandong University (2015WLJH51), the Shandong Provincial Natural Science Foundation (ZR2012HQ033), and the National Natural Science Foundation (81302496).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
128
13
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 20 publications
22
128
13
9
Order By: Relevance
“…Smoking prevalence among adolescents who reported parental smoking was higher in South Korea and Vietnam, whereas South Korean adolescents who reported that both parents smoked showed a higher likelihood to initiate cigarette smoking, compared to adolescents in other countries. This association between SHS in the home and adolescent smoking is comparable to those reported in the United States (Mays et al, ) and in 68 other countries (Xi et al, ). Adolescents with one parent who were daily or weekly smokers were more likely to experiment with smoking, and to become daily smokers like their parents.…”
Section: Discussionsupporting
confidence: 86%
“…Smoking prevalence among adolescents who reported parental smoking was higher in South Korea and Vietnam, whereas South Korean adolescents who reported that both parents smoked showed a higher likelihood to initiate cigarette smoking, compared to adolescents in other countries. This association between SHS in the home and adolescent smoking is comparable to those reported in the United States (Mays et al, ) and in 68 other countries (Xi et al, ). Adolescents with one parent who were daily or weekly smokers were more likely to experiment with smoking, and to become daily smokers like their parents.…”
Section: Discussionsupporting
confidence: 86%
“…It can be observed that relatively high rates of SHS are experienced by the rural Vietnamese participants in our study. Our result is also higher compared to the study with adolescents aged 12–15 in 68 low- and middle-income countries, which showed a total SHS rate of 55.9% [26]. …”
Section: Discussioncontrasting
confidence: 80%
“…The study by Xi et al (11) brings together some important information on adolescent tobacco use and second-hand smoke (SHS) exposure in LMICs. Data from two schoolbased surveys of 12-15-year-olds provide information on over 300,000 adolescents in 68 countries in six WHO regions.…”
mentioning
confidence: 99%
“…In their analysis of LMIC data and the identification of concerning tobacco use rates among adolescents, particularly in the Western Pacific, Xi et al (11) highlight some of the key principles of tobacco control for adolescent populations. Many smokers start at a very young age (<11 years), high adolescent smoking rates are associated with high adult smoking rates and poor enforcement of standard tobacco control measures means that smoking rates in young people remain high.…”
mentioning
confidence: 99%
See 1 more Smart Citation